Spondias mombin supplementation attenuated cardiac remodelling process induced by tobacco smoke - Lourenço, Maria Angélica Martins [UNESP]; Braz, Mariana Gobbo [UNESP]; Aun, Aline Garcia [UNESP]; Pereira, Bruna Letícia Buzati [UNESP]; Figueiredo, Amanda Menezes [UNESP]; da Silva, Renata Aparecida Cândido [UNESP]; Kazmarek, Elisa Moya [UNESP]; Alegre, Patrícia Helena Correa [UNESP]; Bachiega, Tatiana Fernanda [UNESP]; Zanati, Silmeia Garcia [UNESP]; Azevedo, Paula Schmidt [UNESP]; Polegato, Bertha Furlan [UNESP]; et al. (Wiley, 2018)
The objective of this study was to investigate the influence of Spondias mombin (SM) supplementation on the cardiac remodelling process induced by exposure to tobacco smoke (ETS) in rats. Male Wistar rats were divided into 4 groups: group C (control, n = 20) comprised animals not exposed to cigarette smoke and received standard chow; group ETS (n = 20) comprised animals exposed to cigarette smoke and received standard chow; group ETS100 (n = 20) received standard chow supplemented with 100 mg/kg body weight/d of SM; and group ETS250 (n = 20) received standard chow supplemented with 250 mg/kg body weight/d of SM. The observation period was 2 months. The ETS animals had higher values of left cardiac chamber diameters and of left ventricular mass index. SM supplementation attenuated these changes. In addition, the myocyte cross-sectional area (CSA) was lower in group C compared with the ETS groups; however, the ETS250 group had lower values of CSA compared with the ETS group. The ETS group also showed higher cardiac levels of lipid hydroperoxide (LH) compared with group C; and, groups ETS100 and ETS250 had lower concentrations of LH compared with the ETS group. Regarding energy metabolism, SM supplementation decreased glycolysis and increased the β-oxidation and the oxidative phosphorylation. There were no differences in the expression of Nrf-2, SIRT-1, NF-κB, interferon-gamma and interleukin 10. In conclusion, our results suggest that ETS induced the cardiac remodelling process. In addition, SM supplementation attenuated this process, along with oxidative stress reduction and energy metabolism modulation.
Keywords: cardiac remodelling; cigarette smoke; energy metabolism; fruit; oxidative stress